2016
DOI: 10.5897/jdoh2016.0199
|View full text |Cite
|
Sign up to set email alerts
|

Salivary flow rate in adult Kenyans and its relationship with chronic periodontitis

Abstract: The study is aimed at determining the salivary flow rate (SFR) in adult Kenyans and investigates its relationship with chronic periodontitis. A descriptive cross sectional study was conducted on 333 participants (age between 18 and 45 years) among the patients attending Nairobi University Dental Hospital over a period of five months. Three groups were identified based on their periodontal status as healthy, gingivitis and chronic periodontitis. Unstimulated whole saliva was collected using the spit method. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…An increase in saliva flow rate could be in part attributed to an increase in gingival crevicular fluid and body's mechanism by increasing the saliva flow rate to deliver inflammatory mediators and immune cells to the site of infection. 14 From the current research results, it can be seen that there were significant differences in calcium levels of the healthy periodontal group and the periodontitis group. The previous study suggested that it was possibly caused by concentrated calcium in saliva, indicating the severity and development of periodontal disease.…”
Section: Discussionmentioning
confidence: 60%
“…An increase in saliva flow rate could be in part attributed to an increase in gingival crevicular fluid and body's mechanism by increasing the saliva flow rate to deliver inflammatory mediators and immune cells to the site of infection. 14 From the current research results, it can be seen that there were significant differences in calcium levels of the healthy periodontal group and the periodontitis group. The previous study suggested that it was possibly caused by concentrated calcium in saliva, indicating the severity and development of periodontal disease.…”
Section: Discussionmentioning
confidence: 60%